Proterozoic evolution of the northeastern Canadian Shield: Lithoprobe Eastern Canadian Shield Onshore-Offshore Transect (ECSOOT), introduction and summary - Wardle, R J; Hall, J (Canadian Journal of Earth Sciences, 2002)
The Lithoprobe Eastern Canadian Shield OnshoreOffshore Transect (ECSOOT) has focused on studies of the processes by which the northeastern Canadian (Laurentian) Shield evolved, firstly by the 1.91.8 Ga coalescence of Archean cratons and then by the addition of juvenile crust from the south in the period 1.90.9 Ga. The transect area is a microcosm of continental accretion and also offers a unique opportunity to link the geological evolution of the Canadian Shield with once-adjacent Greenland.